2019
DOI: 10.1016/j.apsb.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Development of the triazole-fused pyrimidine derivatives as highly potent and reversible inhibitors of histone lysine specific demethylase 1 (LSD1/KDM1A)

Abstract: Histone lysine specific demethylase 1 (LSD1) has been recognized as an important modulator in post-translational process in epigenetics. Dysregulation of LSD1 has been implicated in the development of various cancers. Herein, we report the discovery of the hit compound 8a (IC 50 = 3.93 μmol/L) and further medicinal chemistry efforts, leading to the generation of compound 15u (IC 50 = 49 nmol/L, and K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 64 publications
0
22
0
1
Order By: Relevance
“…The synthetic route of the title compounds is demonstrated in Scheme 1 . The starting chlorides 1 were prepared from 4,6-dihydroxy-2-mercaptopyrimidine within 6 steps according to the previously reported methods 14 , 15 , 16 . And the target compounds 3 – 24 were readily prepared in 70%–90% yields by reacting 1 with different amines 2 under alkaline conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic route of the title compounds is demonstrated in Scheme 1 . The starting chlorides 1 were prepared from 4,6-dihydroxy-2-mercaptopyrimidine within 6 steps according to the previously reported methods 14 , 15 , 16 . And the target compounds 3 – 24 were readily prepared in 70%–90% yields by reacting 1 with different amines 2 under alkaline conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, based on previously reported LSD1 inhibitors and co-crystal structures, we proposed the ‘2 + 1’ model for the development of new LSD1 inhibitors, highlighting the heterocycles bearing an amine group as a class of emerging scaffolds targeting LSD1 19 , 20 . Based on this proposed model, we have successfully designed different types of LSD1 inhibitors that meet with this model 15 , 21 , 22 , 23 . Considering that the title compounds also featured the heterocyclic scaffold equipped with an amine group, we evaluated the inhibitory activity against LSD1, but found that compound 19 was inactive against LSD1 (IC 50 > 100 μmol/L, Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dificultando ainda mais, em geral, menos de 0,01 % dos protótipos de compostos bioativos sintetizados nos laboratórios têm sucesso nas etapas préclínicas, que compreendem os ensaios biológicos in vitro realizados após a etapa de síntese, purificação e caracterização. [1][2][3][4][5] Dentro deste contexto, sintetizar compostos contendo um núcleo 1,2,3-triazólico em sua estrutura molecular (1-13) é uma estratégia eficiente e amplamente explorada [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] para obtenção de novas moléculas com variadas atividades biológicas, como: antiviral [26][27][28][29] , antídoto 30,31 , antiinflamatória 32 , antibacteriana 33 , antitumoral 34,35 e antimicrobiana 36 (Figura 2). Dentre as vantagens de se incorporar este heterociclo, de origem estritamente sintética, na estrutura molecular do produto planejado destacam-se: (i) podem interagir com diferentes receptores biológicos através de ligações de hidrogênio e/ou interações hidrofóbicas do tipo π-stacking com resíduos de aminoácidos como a fenilalanina; (ii) podem atuar como elos de união entre duas moléculas (linkers), possibilitando a obtenção de compostos híbridos; (iii) podem ser introduzidos na estrutura molecular de um composto como um bioisóstero, por exemplo, na substituição de uma função amida, a fim de evitar reações de hidrólise.…”
Section: Introductionunclassified
“…CDK4, one of the main controllers of cell cycle entry, is substantially overexpressed in glioblastoma, breast and ovarian cancers, making it an attractive therapeutic target 27 , 28 , 29 . Some recent efforts have generated promising leads by targeting compounds to allosteric binding sites in CDKs 30 , 31 , 32 , 33 . The allosteric pocket varies among CDKs, in contrast to the highly conserved ATP-binding site.…”
Section: Introductionmentioning
confidence: 99%